Diagnostic Dilemma in Two Cases of Hyperandrogenism - Ibrahim Alali; Lilianne Haj Hassan; Ghadeer Mardini; Nermeen Hijazi; Lama Hadid; Younes Kabalan (Case Reports in Endocrinology)
Hirsutism is a common endocrine complaint affecting about 10 percent of women. It may be caused by multiple etiologies including adrenal and ovarian disorders. Usually, it is a result of a benign entity such as PCOs and idiopathic hirsutism. However, sometimes especially when it is severe and rapid in progression an androgen-secreting tumor should be excluded. Sertoli-Leydig cell tumors constitute fewer than 0.5 percent of ovarian tumors and it may be benign or malignant. In this article, we present two cases of hyperandrogenism caused by occult ovarian Leydig cell tumors. one of them was confounded by the presence of coincidental bilateral adrenal nodules that complicated the diagnostic process. Tumor dissection was curative in both cases and the diagnosis was confirmed by pathological and hormonal testing after surgery.